Dark of night [large type] - Coble, Colleen (Coble, Colleen. Annie Pederson novel, 2023)
"As if the last few months haven't been hard enough--complete with threats on her life and the return of her first love, Jon--Annie has to figure out whether or not to believe a woman who claims to be her sister, Sarah, who was abducted twenty-four years ago at age five. Annie's eight-year-old daughter, Kylie, has plenty of questions about what's going on in her mother's life--but there are some stones Annie doesn't want uncovered. As Annie grapples with how to heal the gulf between her and her would-be sister and make room in her daughter's life for Jon, she's professionally distracted by the case of yet another missing hiker in Michigan's Upper Peninsula. A woman named Michelle Fraser has now been abducted, and though the woman's estranged husband is at the top of their suspect list, Annie and her colleagues will need to dig deeper and determine whether these recent mysteries are truly as unrelated as they seem." --